Constructions of subalternities and deconstructions of normative discourses in some characters in Los Peor (1995) by Fernando Contreras Castro - Arroyo-Carvajal, Yordan (2023)
This article analyzes the constructions of the subalternities of the characters in the novel Los Peor (1995), by Fernando Contreras Castro, and the deconstructions of the normative and traditional discourses that are integrated into the identity of the subjects subordinated. As a theoretical framework, in their respective chronological order, we consider the ideas of: Gramsci cited by Modonessi (2012), Montero (2009), Giraldo (2003), Brunner (2001), Foucault (2000), Spivak (1998), Prakash (1997) and Bajtín (1975). This allows to conclude that the way in which the fatality of the characters in this novel is constructed refers to the following questions: Can we speak of subordinate subjects in this work or not? What routes are used for its construction?